Arsenic and the Epigenome: Interindividual Differences in Arsenic Metabolism Related to Distinct Patterns of DNA Methylation. Issue 2 (11th January 2013) - Bailey, Kathryn A.; Wu, Michael C.; Ward, William O.; Smeester, Lisa; Rager, Julia E.; García‐Vargas, Gonzalo; Del Razo, Luz‐Maria; Drobná, Zuzana; Stýblo, Miroslav; Fry, Rebecca C.; Slitt, Angela L.; Hodgson, Ernest
ABSTRACT Biotransformation of inorganic arsenic (iAs) is one of the factors that determines the character and magnitude of the diverse detrimental health effects associated with chronic iAs exposure, but it is unknown how iAs biotransformation may impact the epigenome. Here, we integrated analyses of genome‐wide, gene‐specific promoter DNA methylation levels of peripheral blood leukocytes with urinary arsenical concentrations of subjects from a region of Mexico with high levels of iAs in drinking water. These analyses revealed dramatic differences in DNA methylation profiles associated with concentrations of specific urinary metabolites of arsenic (As). The majority of individuals in this study had positive indicators of As‐related disease, namely pre‐diabetes mellitus or diabetes mellitus (DM). Methylation patterns of genes with known associations with DM were associated with urinary concentrations of specific iAs metabolites. Future studies will determine whether these DNA methylation profiles provide mechanistic insight into the development of iAs‐associated disease, predict disease risk, and/or serve as biomarkers of iAs exposure in humans. © 2012 Wiley Periodicals, Inc. J BiochemMol Toxicol 27:106‐115, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/jbt.21462